Diversity, distribution and threat status of Fabaceae plants in Costa Rica: a 135-year herbarium record (UNED Research Journal, 2025)
Introduction: The Fabaceae family is one of the most abundant in Costa Rica, with at least 136 genera and 593 species, many of which are important for agriculture, forestry, and ornamental purposes. Objective: To understand species distribution and extent of collection efforts from the country’s two main herbaria. Methods: We cleaned databases from 1887 to 2022 at the University of Costa Rica (USJ) and the National Herbarium (CR). Results: We documented the presence of 154 genera of Fabaceae, with Inga being the most abundant and diverse. The largest collection effort occurred in 1993, with records of 112 genera and 321 species. We identified 19 species that had not been collected for more than 40 years. Puntarenas emerged as the province with the highest number of genera and species records (117 and 406, respectively), while at the cantonal level, La Cruz, Bagaces, and Osa presented the largest numbers of genera (89, 84, and 79, respectively). Most records are from the Tropical Humid Forest life zone (biotemperature 18-24 °C; precipitation 2 000-4 000 mm). The largest number of species was associated with non-climbing evergreen trees (228 species), followed by non-climbing evergreen shrub/trees (74 species). Additionally, we identified 5 species classified as critically endangered, 29 as endangered, and 21 as near threatened. Conclusion: Our herbarium analysis of Fabaceae in Costa Rica revealed a rich diversity (154 genera, predominantly Inga), with a spatial bias towards Puntarenas and the Tropical Humid Forest. Key findings include 19 long-uncollected species and considerable numbers of threatened species, underlining the need for further conservation efforts and exploration to address taxonomic gaps.
Keywords: legumes; life zones; data science; biodiversity; conservation